Studi Validasi Indeks Massa Tubuh dan Rasio Lingkar Pinggang Panggul terhadap Kadar Glukosa Puasa pada Penerima beasiswa Aktivis Nusantara 2012 - Agus Sholikin; Sri Indratni; Tonang Ardyanto (Nexus Kedokteran Komunitas, 2013)
Agus Sholikin G0009007, 2013. Validation Study of Body Mass Index and Waist to Hip Ratio to Fasting Glucose Rate on Aktivis Nusantara Scholarship Applicants 2012. Mini Thesis Medical Faculty of Sebelas Maret University, Surakarta. Background: Activist students have a little time available for physical exercise from too many activities could cause fat metabolism disorder which increase obesity potential. Body Mass Index (BMI) and Waist to Hip Ratio (WHR) is an easy and cheap antropometry that can be a parameter of metabolic syndrome like hyperglicemia which is caused by obesity. This research aims to find the validity rate between BMI and WHR against Fasting Glucose Rate (FGR) on students who receive Aktivis Nusantara Scholarship 2012. Methods: This was an observational analitic study using cross sectional design. Samples were taken from all applicants of Aktivis Nusantara Scholarsip 2012 by using pure purposive sampling technique. Each subject was taken its BMI, WHR and blood samples to know the FGR after fasting for 10-12 hours. Datas were analyzed and tested with Pearson Correlation test by using Statistical Product and Service Solution (SPSS) 17.0 for Windows. Results: The result of Pearson Correlation Test between BMI and FGR showed P > 0.05, P = 0.785; r = - 0.052. Meanwhile, WHCR and FGR showed P > 0.05, P = 0.874; r = 0.030. Conclusions: We can conclude from this research that WHCR has a higher validity rate than BMI against FGR. Key Word: activist students, validity, BMI, WHCR, FGR